2004
DOI: 10.1002/humu.20003
|View full text |Cite
|
Sign up to set email alerts
|

APECED-causing mutations in AIRE reveal the functional domains of the protein

Abstract: A defective form of the AIRE protein causes autoimmune destruction of target organs by disturbing the immunological tolerance of patients with a rare monogenic disease, autoimmune polyendocrinopathy (APE)-candidiasis (C)-ectodermal dystrophy (ED), APECED. Recently, experiments on knockout mice revealed that AIRE controls autoimmunity by regulating the transcription of peripheral tissue-restricted antigens in thymic medullary epithelial cells. Thus, AIRE provides a unique model for molecular studies of organ-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
105
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 43 publications
11
105
2
2
Order By: Relevance
“…Previously, AIRE was found to activate transcription via heterologous DNA tethering using the Gal.AIRE fusion proteins (14,37,38). In our study, we demonstrated that the free AIRE protein also acted synergistically with GalDBD or Sp1 to activate transcription.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Previously, AIRE was found to activate transcription via heterologous DNA tethering using the Gal.AIRE fusion proteins (14,37,38). In our study, we demonstrated that the free AIRE protein also acted synergistically with GalDBD or Sp1 to activate transcription.…”
Section: Discussionsupporting
confidence: 52%
“…They migrate as a 670-kDa complex, which could contain up to 12 AIRE proteins (14). Monomers of AIRE neither bind DNA in vitro (24,39) nor activate transcription in cells (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems not to operate like a traditional transcription factor, binding to a promoter and/or enhancer element and inducing transcript initiation, but instead to somehow release RNA polymerase (RNA-Pol)II pausing and promote transcript elongation (9,10). Aire targets and regulates genes as a component of one or more large multiprotein complexes (11)(12)(13). Its numerous associates include sets of proteins involved in nuclear transport, chromatin binding/structure, transcription, and pre-mRNA processing (12).…”
mentioning
confidence: 99%